Faktor–Faktor yang Berhubungan dengan Kunjungan Pasca Operasi Sectio Caesare (Sc) - Yunitasari, Eva; SDA, Verina; Sugiyanto , Sugiyanto (Penerbit Goodwood, 2022)
Purpose: The purpose of the study is to know the factors associated with postoperative Sectio Caesarea (SC) visits at the Bumi Waras Hospital, Bandar Lampung City in 2021. Method: This research type is quantitative with a cross-sectional analytic design. The study was conducted at the Bumi Waras Hospital Bandar Lampung in December 2021. The subjects of this study were all mothers who gave birth by cesarean section at the Bumi Waras Hospital in Bandar Lampung. The sampling technique used was total sampling with a total sampling of 295 respondents. The object of this research is age, parity, education, occupation, and history of SC. The data analysis used the Gamma test. Results: The results showed that from 295 respondents who visited as many as 188 (63.7%), respondents with age not at risk were 172 (58.3%), multigravida parity respondents were 186 (63.1%), worked respondents were 154 (52, 2%), no history respondents were 168 (56.9%), secondary education respondents were 167 (56.6%). There was a relationship between age (p-value = 0.001), parity (p-value = 0.002), occupation (p-value = 0.001), history (p-value = 0.002) with post operative cesarean section (SC) visits, and there was no the relationship between education and post operative Sectio Caesarea (SC) visits (p-value = 0.744) at Bumi Waras Hospital Bandar Lampung in 2021.